Fiplac - Mohd Johan, Nur Farhana; Mohd Azmie, Anis Amirah; Mustapakama, Khairunnisa; Mohd Nazri, Nor Anis Ayu; Md Said, Salasiah (Universiti Teknologi MARA, Kedah, 2019)
The idea for this project is coming from the environment in the library where visitors came individually and had meeting at the library. The problem appears when they do not know where their friends at in the library and they feeling lost and not knowing where their friends are will cause some disturbance so that it will making some obnoxious loud calls. If this problem, happen it will just waste the time and it also will cause discomfort to other library user by trying to find their friends. Here is where our innovation came handy, FIPLAC or our innovation would help in reducing sound pollution, save our precious time and help people find their companion to meet up. It can also infuse technology into the library that youngster will be more interested to come to the library.